Sustainability in manufacturing and factories of the future - Herrmann, Christoph; Schmidt, Christopher; Kurle, Denis; Blume, Stefan; Thiede, Sebastian (International Journal of Precision Engineering and Manufacturing-Green Technology, 1(4), 2014)
An increasing global demand for natural resources and the inherent challenges accompanying this demand pose a great task for manufacturing companies. Apart from this, new technologies and a demographic change of the workforce as well as the desire for new individualized products make manufacturing more challenging than ever. To succeed in this new setting manifold perspectives of a factory have been proposed in order to enhance the understanding of the complex interdependencies between the factory elements. Against this background, this paper starts with a short overview regarding the paradigm change in manufacturing including contemporary trends triggering the requirements for factories of the future. Subsequent to that, a selection of factory perspectives is revised indicating the demand for a new holistic perspective of a factory that is more suitable with respect to the new trends. For that reason a new holistic perspective on the factory of the future is presented.